A Sense of the Magical: Names in Lord Dunsany's The King of Elfland's Daughter. (December 2015) - Robinson, Christopher L.
Abstract : Contributing to the enchantment of the author's celebrated prose, the names in Lord Dunsany's best-known novel evoke a world of fairytale, myth, and song; ring true to the characters and places they designate; and fashion themselves into a constellation of correspondences in sound, form, and sense.